ON THE PROBLEM OF DEVELOPING STUDENTS’ WRITING SKILLS - Smailova , Z. (EurasianUnionScientists, 2020)
Nowadays, learning to write is becoming more necessary due to the advent of opportunities to travel, work in foreign companies, participate in international conferences and communicate via the Internet, which requires the ability to express thoughts and ideas in writing. In order to do this wisely, it is necessary to master the basics of the composition, know the stylistic features and follow certain rules of writing organization. At school, this process is not given due attention to, which leads to the appearance of errors of various kinds. These factors determined the relevance of our research.